Biodegradable antibacterial plastic bag and preparation method thereof

By using materials such as polylactic acid and combined with hydrothermal carbonized polymers and SrWO4@Cu,Zn-TCPP composite materials, the problem of insufficient antibacterial properties of existing food packaging bags is solved, and efficient antibacterial and mechanical properties are improved, which is suitable for food packaging.

CN119875336AInactive Publication Date: 2025-04-25GUANG ZHOU HUA RUI HUAN BAO XIN CAI LIAO KE JI YOU XIAN GONG SI

Patent Information

Application Number
CN202510137678.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing food packaging bags have poor antibacterial properties during use, resulting in food being easily contaminated and affecting food quality.

Method used

Materials such as polylactic acid, polycaprolactone, polybutylene terephthalate-butylene adipate and carbonated polymer are used, and carbonated polymers are prepared by hydrothermal preparation and SrWO4@Cu,Zn-TCPP composite materials are prepared to improve the antibacterial and mechanical properties of plastic bags.

Benefits of technology

The prepared antibacterial plastic bags have excellent antibacterial properties and mechanical properties, which can effectively prevent food pollution, extend the shelf life of food, and reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005263782970000071
    Figure BDA0005263782970000071
Patent Text Reader

Abstract

The invention belongs to the technical field of plastics, and particularly relates to a biodegradable antibacterial plastic bag and a preparation method thereof. The material comprises the following raw materials in parts by weight: 20-40 parts of polylactic acid; 60 to 80 parts of polycaprolactone; 50 to 70 parts of poly (butylene adipate-co-terephthalate); 2-6 parts of a carbonized polymer; and 3 to 5 parts of the SrWO4-coated Cu and Zn-TCPP composite material. The carbonized polymer is prepared by adopting a carbon source through a hydrothermal method, the carbonized polymer plays a good role in inhibiting growth of bacteria, the antibacterial performance and mechanical performance of the plastic are improved by preparing tungstate and matching with the MOF material, and the prepared antibacterial plastic bag is excellent in performance, wide in market application and good in prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of plastic technology, and more specifically, relates to a biodegradable antibacterial plastic bag and a preparation method thereof. Background Art

[0002] In the field of food packaging, excessive use of non-degradable petroleum-based packaging materials will not only cause serious environmental pollution, but also the microplastics produced by packaging materials will enter the human body through the food chain, which will pose a serious threat to human health. In order to meet the commercialization and globalization requirements of food supply, the food industry is urged to continuously develop food production, preservation and packaging in a more efficient, convenient and functional direction to maintain product quality. Therefore, ensuring the effective packaging of food during storage and transportation is crucial to the overall quality of food. Commonly used petroleum-based packaging materials are not biodegradable and will affect the ecological environment. In order to extend the shelf life of perishable foods and slow down the environmental pollution caused by the large-scale use of petroleum-based plastics, it is of great significance to develop green, degradable and active fresh-keeping packaging materials based on natural polymers. In the process of using existing food packaging bags, although most of the existing food packaging bags have good tensile properties and are convenient for holding food, due to their poor antibacterial properties, when holding food, the food is easily contaminated and affects the quality of food.

[0003] CN118027622A discloses a high barrier plastic bag with antibacterial functionality and a preparation method thereof. The plastic bag is made of PBAT resin as a base material, starch, barrier inorganic filler, polyfluorine modified material, lubricant and antioxidant as auxiliary materials, and is prepared by mixing, granulating, film blowing and sealing processes. The addition of barrier inorganic filler can not only improve the good barrier performance of the plastic bag, but also give the plastic bag excellent antibacterial performance. The molecular chains of the polyfluorine modified material and the molecular chains of the PBAT matrix are intertwined to form an interpenetrating polymer network structure, which greatly improves the crosslinking density of the PBAT resin and makes the prepared PBAT plastic bag structure more compact, thereby further improving the barrier performance of the PBAT plastic to oxygen and water vapor.

[0004] CN113025008A discloses a wear-resistant plastic bag and a preparation method thereof; the bag is composed of the following raw materials in parts by weight: 100-120 parts of polybutylene succinate and 3-18 parts of wear-resistant masterbatch; wherein the wear-resistant masterbatch comprises the following components by weight percentage: 0.5-0.8% polytetrafluoroethylene, 12-20% composite wear-resistant agent, 0.2-0.4% nano titanium dioxide, 0.25-0.32% stearic acid, 0.5-0.6% polyphenylene ether ketone, 0.3-0 .36%, octadecyl diethanolamine 0.38-0.52%, talc 4.2-5.0%, 2,6-di-tert-butyl-4-methylphenol 0.6-0.75%, coupling agent 0.36-0.55%, plasticizer 0.52-0.6%, and the balance is polybutylene succinate slices; the plastic bag prepared by the present invention not only has good wear resistance, but also has certain sustained-release antibacterial effect, which effectively improves the wear resistance of the prepared plastic bag and prolongs its service life.

[0005] CN112920559A discloses an antibacterial high-strength biodegradable plastic bag and a preparation method thereof, which relates to the technical field of plastic bag preparation. The plastic bag comprises the following components by weight: 110-190 parts of polylactic acid, 320-420 parts of PBAT, 130-150 parts of antibacterial silica particles, 10-50 parts of a chain extender, 20-25 parts of a stabilizer, and 2-6 parts of a silane coupling agent. The invention adopts polylactic acid and PBAT as a matrix, has excellent degradable performance, is environmentally friendly, and has no pollution or burden on the environment. The antibacterial silica particles are used as an additive, which not only increases the overall mechanical properties of the plastic bag and makes it more capable of bearing a greater load, but also increases and gives the plastic bag excellent antibacterial ability, thereby preventing the plastic bag from mildewing and causing harm to the user.

[0006] CN104817750A discloses an antibacterial plastic bag and a preparation method thereof, and relates to the technical field of plastic product manufacturing; the formula of the antibacterial plastic bag is made of the following raw materials in parts by weight: 100 parts of polyethylene, 0.4-0.8 parts of inorganic antibacterial agent, and 0.2-0.4 parts of preservative; the preparation method mainly includes the following steps: after the inorganic antibacterial agent, the preservative and an appropriate amount of polyethylene plastic particles are mixed evenly, extrusion granulation is performed to obtain polyethylene plastic particles with antibacterial and antiseptic functions; after the polyethylene plastic particles with antibacterial and antiseptic functions are mixed evenly with ordinary polyethylene plastic particles, film blowing is performed on an extruder; finally, the plastic film is cut and pressed into plastic bags of various specifications. The present invention can solve the problem that garbage is put into plastic garbage bags and rots and ferments, affecting the quality of the environment.

[0007] From the above content, it can be known that by using degradable materials as raw materials and adding additives with antibacterial properties, a plastic bag with antibacterial properties is obtained by granulating, blowing films, and using a sealing machine to punch the plastic film. The present invention provides a biodegradable antibacterial plastic bag, which has excellent antibacterial properties and mechanical properties by adding homemade antibacterial materials, and has excellent performance and can meet market demand. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a biodegradable antibacterial plastic bag and a preparation method thereof. By weight: it includes the following raw materials: 20 to 40 parts of polylactic acid; 60 to 80 parts of polycaprolactone; 50 to 70 parts of polybutylene terephthalate-adipate; 2 to 6 parts of the carbonized polymer; 3 to 5 parts of the SrWO4@Cu, Zn-TCPP composite material. The present invention uses a carbon source to prepare a carbonized polymer by hydrothermal method, which has a good inhibitory effect on the growth of bacteria. By preparing tungstate and combining it with MOF materials, the antibacterial properties and mechanical properties of the plastic are improved. The antibacterial plastic bag prepared by the present invention has excellent performance, wide market application and good prospects.

[0009] The purpose of the present invention is to provide a biodegradable antibacterial plastic bag.

[0010] Another object of the present invention is to provide a method for preparing a biodegradable antibacterial plastic bag.

[0011] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0012] A biodegradable antibacterial plastic bag comprises the following raw materials by weight: 20-40 parts of polylactic acid; 60-80 parts of polycaprolactone; 50-70 parts of polybutylene terephthalate-adipate; 2-6 parts of carbonized polymer; and 3-5 parts of SrWO4@Cu, Zn-TCPP composite material.

[0013] In the present invention, a preferred embodiment, the method for preparing the carbonized polymer comprises the following steps: dispersing oxalic acid, fumaric acid and ε-polylysine in deionized water, stirring, then performing a hydrothermal reaction, naturally cooling to room temperature, then transferring to a dialysis bag, and purifying in a beaker of ultrapure water, freeze-drying to constant weight to obtain a carbonized polymer.

[0014] Preferably, the mass ratio of oxalic acid, fumaric acid and ε-polylysine is 1-3:2-4:2.

[0015] Preferably, the stirring time is 20 to 40 minutes, and the hydrothermal reaction is carried out at 120 to 140° C. for 8 to 12 hours.

[0016] Preferably, the purification time is 20 to 30 hours, and the freeze-drying temperature is -15°C to -5°C.

[0017] In the present invention, a further preferred embodiment is that the preparation method of the SrWO4@Cu,Zn-TCPP composite material comprises the following steps:

[0018] SrWO4, copper salt, zinc salt and 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in DMF, stirred, and then transferred to a reactor for reaction, centrifuged, washed, and vacuum dried to constant weight to obtain SrWO4@Cu,Zn-TCPP;

[0019] Preferably, the ratio of SrWO4, copper salt, zinc salt and 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) is 10 mg:3-5 mmol:1-3 mmol:1 mmol; the copper salt is one of copper nitrate, copper chloride and copper acetate; the zinc salt is one of zinc nitrate, zinc chloride and zinc acetate.

[0020] Preferably, the stirring time is 20 to 40 minutes, and the reaction condition is 80 to 120° C. for 12 to 20 hours.

[0021] Preferably, the drying temperature is 80°C.

[0022] Based on the above-mentioned method for preparing a biodegradable antibacterial plastic bag, the preparation method comprises the following steps: uniformly mixing the carbonized polymer, SrWO4@Cu, Zn-TCPP composite material, polylactic acid, polycaprolactone and polybutylene terephthalate-adipate, and then feeding the materials into a twin-screw extruder to make granules, and setting parameters as follows: screw speed 240-280rpm, 1-5 zone heating temperatures are as follows: 140-150℃, 150-155℃, 160-170℃, 160-170℃ , 170-180℃; then the granulated material is dried at 60-80℃ for 6-12h to obtain a blown film material, and then put into a blown film machine for blown film molding. The setting parameters are: screw speed 200-240rpm, 1-5 zone heating temperatures are as follows: 130-140℃, 140-150℃, 150-160℃, 165-175℃, 170-180℃, traction speed 9-10m / min, and a plastic film is made. The plastic film is punched with a sealing machine to obtain a degradable plastic bag.

[0023] The present invention has the following beneficial effects:

[0024] The present invention adopts hydrothermal method to prepare carbonized polymer, which will destroy the integrity of cell membrane when in contact with bacteria, causing leakage of substances in cells and causing bacterial death. In addition, carbon materials can produce oxidative groups to cause oxidative stress to microorganisms, thereby playing an antibacterial role. Tungstate has a certain antibacterial effect on bacteria. By using SrWO4 and Cu, Zn-TCPP materials to compound, it can play a good antibacterial effect. In addition, by adding the above components, the mechanical properties of plastic bags can be effectively improved. DETAILED DESCRIPTION

[0025] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0026] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0027] Example 1

[0028] A biodegradable antibacterial plastic bag comprises the following raw materials by weight: 30 parts of polylactic acid; 70 parts of polycaprolactone; 60 parts of polybutylene terephthalate-adipate; 4 parts of carbonized polymer; and 4 parts of SrWO4@Cu, Zn-TCPP composite material.

[0029] The preparation method of the carbonized polymer comprises the following steps: dispersing 2g of oxalic acid, 3g of fumaric acid and 2g of ε-polylysine into 150mL of deionized water, stirring for 30min, then hydrothermally reacting at 130°C for 10h, naturally cooling to room temperature, then transferring to a dialysis bag, purifying in a beaker of ultrapure water for 26h, and freeze-drying at -10°C to constant weight to obtain a carbonized polymer.

[0030] The preparation method of the SrWO4@Cu,Zn-TCPP composite material comprises the following steps:

[0031] 10 mg SrWO4, 4 mmol copper nitrate, 2 mmol zinc chloride and 1 mmol 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 200 mL DMF, stirred for 30 min, and then transferred to a reactor, reacted at 100 °C for 16 h, centrifuged, washed, and vacuum dried at 80 °C to constant weight to obtain SrWO4@Cu,Zn-TCPP.

[0032] A method for preparing a biodegradable antibacterial plastic bag comprises the following steps: uniformly mixing a carbonized polymer, a SrWO4@Cu, Zn-TCPP composite material, polylactic acid, polycaprolactone and polybutylene terephthalate-adipate, feeding the mixture into a twin-screw extruder to form granules, wherein the parameters are set as follows: a screw speed of 260 rpm, and heating temperatures in zones 1-5 are as follows: 145°C, 155°C, 165°C, 168°C, and 175°C; drying the granules at 70°C for 10 hours to obtain a film blowing material, and then feeding the granules into a film blowing machine for film blowing, wherein the parameters are set as follows: a screw speed of 220 rpm, heating temperatures in zones 1-5 are as follows: 135°C, 145°C, 155°C, 170°C, and 175°C, and a pulling speed of 9.5 m / min, and making a plastic film, and performing a notching treatment on the plastic film using a sealing machine to obtain a degradable plastic bag.

[0033] Example 2

[0034] A biodegradable antibacterial plastic bag comprises the following raw materials by weight: 40 parts of polylactic acid; 60 parts of polycaprolactone; 70 parts of polybutylene terephthalate-adipate; 2 parts of carbonized polymer; and 5 parts of SrWO4@Cu, Zn-TCPP composite material.

[0035] The preparation method of the carbonized polymer comprises the following steps: dispersing 3g of oxalic acid, 2g of fumaric acid and 2g of ε-polylysine into 150mL of deionized water, stirring for 40min, then hydrothermally reacting at 140°C for 8h, naturally cooling to room temperature, then transferring to a dialysis bag, purifying in a beaker of ultrapure water for 30h, and freeze-drying at -5°C to constant weight to obtain a carbonized polymer.

[0036] The preparation method of the SrWO4@Cu,Zn-TCPP composite material comprises the following steps:

[0037] 10 mg SrWO4, 5 mmol copper chloride, 1 mmol zinc acetate and 1 mmol 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 200 mL DMF and stirred for 40 min. Then the mixture was transferred to a reactor and reacted at 120 °C for 12 h. The mixture was centrifuged, washed and dried at 80 °C in vacuum until constant weight was obtained to obtain SrWO4@Cu,Zn-TCPP.

[0038] The preparation method of a biodegradable antibacterial plastic bag is the same as that in Example 1.

[0039] Example 3

[0040] A biodegradable antibacterial plastic bag comprises the following raw materials by weight: 20 parts of polylactic acid; 80 parts of polycaprolactone; 50 parts of polybutylene terephthalate-adipate; 6 parts of carbonized polymer; and 3 parts of SrWO4@Cu, Zn-TCPP composite material.

[0041] The preparation method of the carbonized polymer comprises the following steps: dispersing 1 g of oxalic acid, 4 g of fumaric acid and 2 g of ε-polylysine into 150 mL of deionized water, stirring for 20 min, then hydrothermally reacting at 120° C. for 12 h, naturally cooling to room temperature, then transferring to a dialysis bag, purifying in a beaker of ultrapure water for 20 h, and freeze-drying at -15° C. to constant weight to obtain a carbonized polymer.

[0042] The preparation method of the SrWO4@Cu,Zn-TCPP composite material comprises the following steps:

[0043] SrWO4, 3mmol copper acetate, 3mmol zinc nitrate and 1mmol 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 200mL DMF and stirred for 20min. Then the mixture was transferred to a reactor and reacted at 80℃ for 20h. The mixture was centrifuged, washed and dried under vacuum at 80℃ to constant weight to obtain SrWO4@Cu,Zn-TCPP.

[0044] The preparation method of a biodegradable antibacterial plastic bag is the same as that in Example 1.

[0045] Comparative Example 1

[0046] The difference between Control Example 1 and Example 1 is that the preparation method of the carbonized polymer comprises the following steps: dispersing 5 g of fumaric acid and 2 g of ε-polylysine in 150 mL of deionized water, stirring for 30 min, then hydrothermally reacting at 130 ° C for 10 h, naturally cooling to room temperature, then transferring to a dialysis bag, and purifying in a beaker of ultrapure water for 26 h, and freeze-drying at -10 ° C to constant weight to obtain a carbonized polymer.

[0047] Comparative Example 2

[0048] The difference between Control Example 2 and Example 1 is that the preparation method of the carbonized polymer comprises the following steps: dispersing 3 g of fumaric acid and 4 g of ε-polylysine in 150 mL of deionized water, stirring for 30 min, then hydrothermally reacting at 130 ° C for 10 h, naturally cooling to room temperature, then transferring to a dialysis bag, and purifying in a beaker of ultrapure water for 26 h, and freeze-drying at -10 ° C to constant weight to obtain a carbonized polymer.

[0049] Comparative Example 3

[0050] The difference between the control example 3 and the embodiment 1 is that an equal amount of SrWO4@Cu-TCPP composite material is used to replace the SrWO4@Cu, Zn-TCPP composite material, and the preparation method of the SrWO4@Cu-TCPP composite material comprises the following steps:

[0051] 10 mg SrWO4, 6 mmol copper nitrate and 1 mmol 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in 200 mL DMF, stirred for 30 min, and then transferred to a reactor, reacted at 100 °C for 16 h, centrifuged, washed, and vacuum dried at 80 °C to constant weight to obtain SrWO4@Cu,Zn-TCPP.

[0052] Comparative Example 4

[0053] The difference between Control Example 4 and Example 1 is that an equal amount of Cu, Zn-TCPP is used to replace the SrWO4@Cu, Zn-TCPP composite material. The preparation method of the Cu, Zn-TCPP comprises the following steps: 4 mmol copper nitrate, 2 mmol zinc chloride and 1 mmol 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) are dissolved in 200 mL DMF, stirred for 30 min, then transferred to a reactor, reacted at 100° C. for 16 h, centrifuged, washed, and vacuum dried at 80° C. to constant weight to obtain Cu, Zn-TCPP.

[0054] Comparative Example 5

[0055] The difference between Control Example 5 and Example 1 is that an equal amount of SrWO4@Cu, Zn-TCPP composite material is used to replace the carbonized polymer.

[0056] The properties of the plastic bags of Examples 1-3 and Comparative Examples 1-5 were tested. The specific test results are shown in Table 1:

[0057] Among them, tensile strength: tested according to the national standard GB / T 1040.3-2006;

[0058] Antibacterial rate: tested according to standard QB / T2591-2003, the test bacteria is Escherichia coli.

[0059] Table 1

[0060]

[0061] It can be seen from Table 1 that, by comparing Example 1 with Comparative Examples 1-5, the biodegradable antibacterial plastic bag prepared by the present invention has excellent tensile strength and antibacterial effect, and the components of the selected materials interact with each other, which jointly promotes the improvement of the performance of the plastic bag. The antibacterial plastic bag prepared by the present invention has excellent performance, wide market application, and good prospects.

[0062] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A biodegradable antibacterial plastic bag, characterized by: By weight: the following raw materials are included: 20 to 40 parts of polylactic acid; 60 to 80 parts of polycaprolactone; 50 to 70 parts of polybutylene terephthalate-adipate; 2 to 6 parts of carbonized polymer; and 3 to 5 parts of SrWO4@Cu, Zn-TCPP composite material.

2. A biodegradable antibacterial plastic bag according to claim 1, characterized in that: The preparation method of the carbonized polymer comprises the following steps: dispersing oxalic acid, fumaric acid and ε-polylysine in deionized water, stirring, then performing a hydrothermal reaction, naturally cooling to room temperature, then transferring to a dialysis bag, purifying in a beaker of ultrapure water, and freeze-drying to constant weight to obtain a carbonized polymer.

3. A biodegradable antibacterial plastic bag according to claim 2, characterized in that: The mass ratio of the oxalic acid, fumaric acid and ε-polylysine is 1-3:2-4:

2.

4. A biodegradable antibacterial plastic bag according to claim 2, characterized in that: The stirring time is 20 to 40 minutes, and the hydrothermal reaction conditions are 120 to 140° C. for 8 to 12 hours.

5. The biodegradable antibacterial plastic bag according to claim 2, characterized in that: The purification time is 20 to 30 hours, and the freeze-drying temperature is -15°C to -5°C.

6. The biodegradable antibacterial plastic bag according to claim 1, characterized in that: The preparation method of the SrWO4@Cu,Zn-TCPP composite material comprises the following steps: SrWO4, copper salt, zinc salt and 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) were dissolved in DMF, stirred, and then transferred to a reactor for reaction. SrWO4@Cu,Zn-TCPP was obtained by centrifugation, washing and vacuum drying to constant weight.

7. A biodegradable antibacterial plastic bag according to claim 6, characterized in that: The ratio of SrWO4, copper salt, zinc salt and 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) is 10mg:3-5mmol:1-3mmol:1mmol; the copper salt is one of copper nitrate, copper chloride and copper acetate; the zinc salt is one of zinc nitrate, zinc chloride and zinc acetate.

8. The biodegradable antibacterial plastic bag according to claim 6, characterized in that: The stirring time is 20 to 40 minutes, and the reaction condition is 80 to 120° C. for 12 to 20 hours.

9. The biodegradable antibacterial plastic bag according to claim 6, characterized in that: The drying temperature is 80°C.

10. A method for preparing a biodegradable antibacterial plastic bag according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: uniformly mixing a carbonized polymer, a SrWO4@Cu, Zn-TCPP composite material, polylactic acid, polycaprolactone and polybutylene terephthalate-adipate, feeding the materials into a twin-screw extruder to form granules, drying the granules to obtain a film blowing material, and then feeding the granules into a film blowing machine for blow molding to form a plastic film, and using a sealing machine to perform a notch treatment on the plastic film to obtain a degradable plastic bag.

Citation Information

Patent Citations

  • Antibacterial plastic bag and preparation method thereof

    CN104817750A

  • Antibacterial high-strength biodegradable plastic bag and preparation method thereof

    CN112920559A

  • Wear-resistant plastic bag and preparation method thereof

    CN113025008A

Cited By

  • Preparation method of long-acting antibacterial multilayer composite fresh-keeping packaging film

    CN121552719A